PENGARUH PENGGUNAAN SOFTWARE AUDIT DAN ROLE AMBIGUITY TERHADAP KINERJA AUDITOR - Astried Debora Manurung; Ali Djamhuri (Jurnal Akuntansi dan Keuangan, 2024)
This study aims to investigate the effect of audit software usage and role ambiguity on auditor performance at RSM Indonesia Public Accounting Firm. Audit software is considered a technological innovation that can accelerate and improve the efficiency of the audit process, while role ambiguity is identified as a psychological factor that can affect the implementation of auditor duties. This study uses an empirical study approach by applying a survey method to auditors working at RSM Indonesia Public Accounting Firm. Data were collected through questionnaires to measure the use of audit software, the level of auditor role ambiguity, and auditor performance. Data analysis was performed using regression techniques to identify relationships between variables. The results showed that the use of audit software has a positive effect on auditor performance and the ambiguity of the auditor's role has a negative effect on auditor performance. The results of this study are expected to provide valuable insights into how the use of audit software and role ambiguity affect auditor performance at RSM Indonesia Public Accounting Firm.